Perencanaan konsep event festival kampung tangerang dalam membangun citra pada mall cbd ciledug - Astuti, Apriliyanti (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2019)
In general, a trade center need to showcase something unique and special to attract guests and tenants. â€œFESTIVAL KAMPUNG TANGERANGâ€ is a concept of public relations strategy which is created by the conceiver to build the image of CBD Ciledug Mall to attract more traffic to visit. In the making of this concept, the conceiver already conducted pre-research by interviewing customers, tenants and management of the CBD Ciledug Mall to get the idea for the concept to be developed further. This concept is based on Ronald D. Smith Theory which helps the conceiver in building and road map which is needed to make this concept. The final outcome of this concept still needs to be discussed with the Mall Management for further if it is going to be made into an event.Keywords: Tangerang city; shopping mall; CBD Ciledug Mall